(untitled) (Praxis Educativa, 2025)
The purpose of this article is to expose some serious problems with the Trump administration’s plans to dismantle the Department of Education under the watchful eye of Project 2025, a blueprint for a radical reimagining of government based on ideas as dangerous as they are destructive. This is a long-standing obsession, and giving it shape would be akin to setting fire to the foundations of American education and would leave scars on students, schools, and the very soul of learning. Will the administration ultimately succeed in bringing down the Department of Education? What will be the locus of resistance? Keywords: Department of Education, public education, ideology, indoctrination